Electron Ionization Based Detection of Volatile Constituents of Aerial Parts of Eclipta prostrata (Linn.) by One Dimensional Gas Chromatography and Mass Spectrometry. Issue 3 (3rd May 2020) - Sahoo, Suprava; Singh, Subhashree; Dash, Manaswini; Jena, Sudipta; Sahoo, Ambika; Nayak, Sanghamitra; Kar, Basudeba
Abstract: Eclipta prostrata (Linn.) (Family: Asteraceae ) is an important Indian medicinal herb having myriad therapeutic potential. In the present study, the essential oil was extracted from the aerial parts of E. prostrata collected from 10 different regions of Odisha by hydro-distillation and analyzed by using one- dimensional gas chromatography coupled with mass spectrometry (GC/MS). Fifty nine volatile compounds comprising 68.84-96.58% of the total oil were identified. Sesquiterpene hydrocarbons were the predominant group of compounds which varied from 26.84-62.67% followed by monoterpene hydrocarbons (28.93-38.66%). The E. prostrata oils were rich in α-pinene (11.2 - 18.23%) followed by caryophyllene (8.56 - 15.38%), α- humulene (1.8-11.1%), α-pinene (2.6 - 8.72%), camphene (2.6 - 8.5%), allo-aromadendrene (2.5 - 6.99%), α-amorphene (0.3 - 7.8%), cis -muurole-4(14), 5-diene (1.2 - 5.7%), eugenol (2.13 - 4.1%) followed by other minor compounds. The major constituents of all the studied germplasms displayed the same major compounds in their essential oil with varying area percentage. Hence, with having these well known bioactive phytoconstituents, the essential oil of E. prostrata would have enough significance in the food and pharmaceutical industries.